The Invisible Lives of Chaplains of Color - Giles, Cheryl (Journal of pastoral theology, 2022)
Chaplains of color take care of their own spiritual, emotional, and physical wellbeing while caring for others, who are experiencing pain, anguish, and suffering. In many ways, these chaplains struggle with a triple whammy as they provide caregiving in uncharted water: being a person of color and a caregiver during a time of heightened racial tension and violence, feeling invisible, and disrespected. The toll on chaplains of color may not be visible, but it is there. They hold embodied trauma from implicit bias. Being present to others, is more than just showing up. It requires an ability to manage one’s own vulnerability as life continues to unfold. Often this means getting unhooked from the emotional patterns that we have developed and those that control us.